HUBUNGAN TINGKAT PENGETAHUAN RESPONDEN DENGAN PEMILIHAN OPERATOR SELAIN DOKTER GIGI DITINJAU DARI BAHAYA PEMASANGAN ALAT ORTODONTIK - Cecep Hadyan Khairusy; Rosihan Adhani; Diana Wibowo (FKG Unlam, 2017)
Background: Orthodontic treatment is increasingly in demand by the public. Orthodontic treatmentperformed by an operator other than dentists who are competent if it’s not appropriate with properlymaintenance procedures will cause adverse impacts. Purpose: The objectives of this study are knowing therespondent’s level of knowledge about bad impacts of orthodontic mounting and knowing the correlationbetween respondent’s level of knowledge with operator choice beside dentist. Method: This study was anobservational analytical with cross sectional approach. This study was done to 30 students of SMAN 2Banjarmasin. Result: When the study and analyze data were done, the result was most of respondent have levelof knowledge in good category, they were 24 students (80%), Conclusion : There is correlation betweenrespondent’s level of knowledge with operator choice based on bad impacts of orthodontic mounting.Keywords : Level of Knowledge, Operator Choice, Bad Impacts of Orthodontic Mounting